Halal authentication of alcohol in food and beverages products: a review - Mohamad Ikhiwan, Nur Hanisah; Tukiran, Nur Azira (UiTM Press, 2024)
In recent years, the global halal food sector has developed significantly, as the halal industry's safety, cleanliness, and quality assurance are essential to Muslim life. The presence of alcohol in particular food and beverage products may raise doubts among some individuals; it is crucial to recognize that Islamic teachings explicitly prohibit the consumption of intoxicants. However, a nuanced exploration of Islamic legal frameworks reveals that minute amounts of alcohol utilized in food processing may be deemed permissible, provided that they do not reach intoxicating levels. Precision in adhering to these thresholds demands that consultation with scholarly authorities well-versed in Islamic jurisprudence can offer clarity and guidance, ensuring adherence to Islamic principles. This paper aims to review alcohol and the amount of permissible usage in food and beverages as discussed by Muslim scholars and to ascertain and validate the presence of alcohol in food and beverage products, ensuring that it is appropriate for Muslim consumption. Various analytical methods have been developed to confront this issue, including using gas chromatography, mass spectrometry, electronic nose, and a combination of machine learning algorithms, biosensors, and specific gravimetry methods. Although innovative techniques have been developed, the intricacies of analyzing alcohol within complex food matrices stem from various contributing factors. The presence of sugars introduces molecular interactions that can affect the stability and detection of alcohol, which pose challenges to inaccurate quantification. Additionally, fibrous materials within these matrices may impede the extraction and measurement of alcohol, adding another layer of complexity. The diverse array of substances, including fats, proteins, and additives, further complicates the solubility and separation of alcohol during analysis, necessitating advanced methodologies for precise evaluation. Ease of access to information also misleads consumers into false facts on specific issues regarding halal products.